KELEMBAGAAN PEMASARAN DAN KEMITRAAN KOMODITI SAYURAN Kasus di Desa-Desa di Jawa Tengah dan Sumatera Utara - Endang Lestari Hastuti (SOCA: Jurnal Sosial Ekonomi Pertanian, 2004)
Institutional of Vegetable Commodity Marketing and Partnership: Cases in Villages ofCentral Java and North Sumatra. Although agribusiness is the biggest contributor of foreignexchange earnings, however, volume of imported vegetables and fruits tent to increase. Thissituation triggered some disadvantageous suppression on farm gate prices. The results of theresearch conducted in villages of Central and North Sumatra showed that national vegetableproducts could not compete with other country’s products. National trading pattern consistedof wholesale trading, medium scale trading and small scale trading. Marketing cost wasrelatively high while community’s accessibility on formal financing institutional was quitelow. Most traders served partnerships with farmers to maintain supply continuity in the meantime farmers could get capital for input production and marketing security. Consumer’s pricewas very fluctuate due to perishable natures and it is concentrated in a region. Consequently,relationship functions among agribusiness agents is required as well as storage facilities in theagribusiness centers.